Biochemical analysis of candidate probiotic bacteria was isolated from the digestive tract of the Banana shrimp (Penaeus merguiensis) - Raharja, Hendra; Zubaidah, Anis; Prasetyo, Dony (Universitas Malikussaleh, 2023)
In nature, there are many types of bacteria that can act as probiotics. These bacteria can come from soil, water, plants or even the digestive tract of animals. This study aims to analyze the biochemical characteristics of probiotic candidate bacteria originating from the digestive tract of giant prawns. The method used is a descriptive explorative method to perform biochemical analysis of the types of probiotic bacteria derived from jerbung shrimp. The biochemical analysis included the Catalase test, Oxidase test, Urea test, Citrate test, TSIA, Methyl red, Voges-Proskaeurs, and sugar fermentation test (D-Glucose, Sucrose, Inositol, Manisitol. Laboratory analysis results showed that the isolated bacteria had morphological characteristics rod-shaped, gram-positive, does not produce catalase and oxidase enzymes, but can produce citric enzymes. These bacteria are acidic, capable of fermenting glucose, sucrose, inositol, and mannitol. The conclusion of this study, probiotic candidate bacteria from the test results showed compatibility with Lactobacillus sp bacteria.Keywords: isolation; probiotics; shrimp